The STEAM approach and its pedagogic and methodological trends (Research, Society and Development, 2022)
This research aimed to identify the pedagogical and methodological trends obtained in recent years in STEAM education (Science, Technology, Engineering, Arts and Mathematics) in science and mathematics teaching. A survey of theses and dissertations was carried out in the Bank of Theses and Dissertations of Capes, from 2018 to 2021, through analysis of a Systematic Review on the topic of interest. Through this survey, 15 works were selected and analyzed that were in accordance with the proposed objective, that is, works with a STEAM approach aimed at teaching Physics, Chemistry and Biology. In this way, it was possible to identify two categories, one referring to the teaching proposal and the other about teaching and learning methodology/approach that resulted in subtopics with different educational modalities, providing students with a protagonist role in the learning process. Research on STEAM education in Brazil is still scarce, from this research we can observe some gaps and shortcomings, so this theme needs to be explored in science and mathematics teaching.